Witches and Princesses in “La Mica”, by Carmen Lyra: Feminist Reading - Robles Murillo, Keylor (2020)
This article analyzes the representation of witches and princesses in the story "La mica", from the book Cuentos de mi tía Panchita (1920), by Carmen Lyra. For this purpose, a series of sections are established. First, the critical apparatus by which the text is approached, corresponding to the feminist literary and the defined object of study, is pointed out. Secondly, the author and her work are located within their political, social, economic and cultural context. Third, two mediation strategies are included: intertexts and inter-discourses, in order to elucidate the analysis. Fourth, the social and ideological implications of the discourses inherent in the story are pointed out. Finally, the conclusions obtained from the approach are provided.